Anatomical characterization of Portulaca grandiflora Hook: Root, stem, leaf, and pollen structures - Rahayu, Tri; Ermayanti, Ermayanti (Bioma : Berkala Ilmiah Biologi, 2025)
Portulaca grandiflora Hook. is a succulent plant commonly used as an ornamental as well as a medicinal plant. This species is capable of growing well under suboptimal climatic conditions and in poor soil compositions. This study aims to identify the tissue composition of various organs of P. grandiflora Hook., which can be utilized in the processes of identification, classification, and understanding its ecological adaptability. Anatomical observations were carried out using the free-hand section method to examine cross-sectional anatomy of roots, stems, and the epidermal tissue of leaves on both the adaxial and abaxial surfaces. Additionally, the acetolysis method was employed to observe the pollen structure. The results showed that the root cross-section consists of epidermal tissue, cortex, endodermis, pericycle, xylem, and phloem. The stem cross-section includes epidermal tissue, cortex with starch-containing parenchyma cells, pith, and vascular bundles of the open collateral type. The leaf epidermis, both on the adaxial and abaxial surfaces, consists of polyhedral epidermal cells with undulating cell walls. The type of stomata observed was parasitic, with an amphistomatic distribution. Pollen observation revealed that the pollen grains are spherical, have echinate ornamentation, and possess a monoporate aperture.